Phi-feature in Kulung - Rai, Reena (Kirat Pragya किरात प्रज्ञा, 2026)
This paper examines phi features in Kulung, a Central Kiranti language of the Himalayan branch of the Trans Himalayan language family spoken by the Rai community in eastern Nepal and in parts of eastern and southern Sikkim, India, where it is endangered. It describes the realization of person, number, clusivity, and dimension in the verbal agreement system. The study is based on primary data from fieldwork in Assam Lingzey, East Sikkim, supported by earlier descriptive studies. The analysis shows that Kulung has a rich pronominal verbal morphology that encodes three persons and three numbers, namely singular, dual, and plural, and marks the inclusive and exclusive distinction in first-person non-singular forms. Gender is expressed lexically, while grammatical gender is absent in both nominal morphology and agreement. These findings contribute to the typological understanding of phi feature marking in Kiranti languages and highlight the need to document endangered Trans-Himalayan languages.